An Intermittently Used Two-Unit System with Semi-Markov Need Process - MOOSA, Sharafali (Institutional Knowledge at Singapore Management University, 1993)
An intermittently used two-unit system with a single repair facility is considered. The number of units required for the system performance at any time is governed by a particular semi-Markov process. Identifying suitable regeneration points, expressions are obtained for the distribution function of the time to the first disappointment and the mean rate of disappointments.